THE EFFECTIVENESS OF PROBLEM-BASED LEARNING MODEL BASED ON A SCOUTING METHOD ON LEARNING OUTCOMES IN PHYSICS SUBJECTS - Roziqin, Roziqin; Sugianto, Sugianto (UPEJ Unnes Physics Education Journal, 2023)
The challenges of education in the 21st century are characterized by a very complex century of openness. The curriculum used must be able to keep up with the times that require the brain intelligence and talents of students. The researcher tried to apply the problem-based learning model based on the scouting method which was described as fun and not boring method. The purpose of this study was to determine the effectiveness of the problem-based learning model based on scouting methods on student learning outcomes in physics subjects. The research used the true experimental design method with a pretest-posttest control group design, conducted at SMAN 1 Wonotunggal on XI IPA 1 as the experimental class and XI IPA 3 as the control class. Data collection techniques include cognitive assessment, affective and psychomotor assessment, and a questionnaire. The results obtained in the cognitive domain in the form of tests are that there are significant differences in learning outcomes with the t test. In the affective domain in the form of spiritual and social attitudes, the experimental class gets a very good category, while the control class gets a good category. In the psychomotor domain in the form of student skills, the experimental class got a percentage of 92.5%, while the control class got a percentage of 90%. This shows that there is a significant difference between the problem-based learning model based on scouting methods and those that only use the problem-based learning model. On improving learning outcomes, the experimental class got a percentage of 92%, while the control class got a percentage of 90%. This shows that there is a significant difference between the problem-based learning model based on the scouting method and the one that only uses the problem-based learning model. In improving learning outcomes using a problem-based learning model based on scouting methods, an increase in N-gain value of 24.5% was obtained in the low category. This shows that in this study, there was an increase in student learning outcomes. In the satisfaction response results, students were satisfied with a percentage of 79.82%. Keywords: Problem-Based Learning, Scouting Methods, Learning Outcomes, Physics.